PROTECTION OF CONFIDENTIAL MEDICAL INFORMATION IN UKRAINE: PROBLEMS OF LEGAL REGULATION - Onishchenko, N; Teremetskyi, V; Kolesnikov, A; Kovalchuk, O; Shabalin, A; Romas, M (Georgian medical news, 2024)
The aim of the article is to analyze the legal aspects and mechanisms of confidential medical information protection about an individual in the health care sphere in Ukraine. During the scientific research, various methods of cognition of legal phenomena were used. Among the general scientific approaches, the dialectical method was primarily used, which allowed to identify trends in the development of patient information rights and formulate proposals for improving legislation in the field of medical data protection. The formal-legal method was used to provide a comprehensive characterization of the EU (European Union) and Ukrainian legislation in the sphere of confidential medical information protection. Additionally, general scientific logical methods (analysis and synthesis, comparison and analogy, abstraction, and modeling) were used in order to study the problems of information relations in the medical field and establish legal liability for violation of the confidentiality of such information. The definitions of medical data, medical information, confidential medical data, and medical confidentiality have been researched and compared. The article identified the legitimate grounds for disclosing confidential medical information about an individual in the healthcare sector. Authors revealed the gaps in Ukrainian legislation regarding the confidential medical data protection by healthcare professionals and electronic medical systems regulators. The necessity of expanding the list of subjects responsible for preserving confidential medical information has been substantiated. The study explored the case law of the European Court of Human Rights in the field of the medical data confidentiality violation. It has been outlined the potential judicial remedies and liability for violating the right to personal medical information confidentiality of an individual in the healthcare sector. The legal grounds and cases of possible lawful disclosure of confidential medical information have been analyzed. Attention has been drawn to the insufficient regulation of access to medical confidentiality during martial law. It has been emphasized that the mechanism for protecting the violated right to confidentiality of medical information involves appealing to the Ukrainian Parliament Commissioner for Human Rights or to the court. The increasing role of international legal acts in ensuring the protection of medical data in the European Union and Ukraine has been highlighted.